2014
DOI: 10.1007/s12639-014-0453-3
|View full text |Cite
|
Sign up to set email alerts
|

Survey on efficacy of chloroformic extract of Artemisia annua against Giardia lamblia trophozoite and cyst in vitro

Abstract: Giardiasis is a parasitic cosmopolitan disease that the rate of infection in developing countries is considerable. This infection directly is associated with poor hygienic conditions, poor water quality control, and overcrowding. Reinfection and drug resistance are two major problems in endemic areas. Recently, researchers are concentrating on herbal drugs as a proper solution. Therefore, the objective of the present study was to survey on efficacy of chloroformic extract of Artemisia annua against Giardia lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Bavand et al (2014) has studied the effect of gold nanoparticles in the three concentrations of 0.05, 0.1 and 1.3 ppm on the human isolates of Giardia lamblia cyst. In that study, the researchers have compared the effects of gold nanoparticles with Metronidazole (positive control group) (Golami et al 2016). The results of this study have shown that gold nanoparticles in concentration of 0.3 were able to destroy 96% of this G. lamblia within 180 min while the Metronidazole destroyed 99% of this parasite which there is no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Bavand et al (2014) has studied the effect of gold nanoparticles in the three concentrations of 0.05, 0.1 and 1.3 ppm on the human isolates of Giardia lamblia cyst. In that study, the researchers have compared the effects of gold nanoparticles with Metronidazole (positive control group) (Golami et al 2016). The results of this study have shown that gold nanoparticles in concentration of 0.3 were able to destroy 96% of this G. lamblia within 180 min while the Metronidazole destroyed 99% of this parasite which there is no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…The encysted stage of the organism is relatively resistant to chlorination and ozonolysis can remain viable for several weeks. Humans are considered as the most significant reservoir hosts for human giardiasis (Adam 2001;Al-Mekhlafi et al 2013), with outbreaks occasionally occurring due to mass exposure to insanitry water and food containing cysts of the parasite and direct contact with infected individuals, particularly in child care centers (Gholami et al 2016). Giardiasis is of particular concern in developing countries with a prevalence ranging from 20 to 60% compared to 2-7% in industrialized countries (Faraji et al 2015;Yakoob et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This nding is in line with Alin and Bjorkman [64] observation who demonstrated that artemisinin, an Artemisia annua derivative, inhibited the growth of malaria parasite in a concentration dependent manner. Additionally, in vitro experiments of [45] demonstrated that Artemisia annua extracts destroyed giardia trophozoites in concentration and time dependent manners. Therefore, reduction of Giardia lamblia trophozoite counts after treatment with Artemisia annua extracts could be through inhibition of its growth and/or direct killing of trophozoites by Artemisia annua.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Artemisia annua has showed effectiveness against trypanosomiasis [39], schistosomiasis [40], toxoplasmosis [41], leishmaniasis [42,43] and coccidiosis [44]. Additionally, in vitro experiments have shown that extracts of Artemisia annua plant were effective against Giardia lambliain vitro [45].…”
Section: Introductionmentioning
confidence: 99%